2021
DOI: 10.2214/ajr.21.25508
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Imaging of Pediatric Pancreatitis: AJR Expert Panel Narrative Review

Abstract: Pancreatitis is as common in children as it is in adults, though causes and accepted imaging strategies differ in children. In this narrative review we discuss the epidemiology of childhood pancreatitis and key imaging features for pediatric acute, acute recurrent, and chronic pancreatitis. We rely heavily on our collective experience in discussing advantages and disadvantages of different imaging modalities; practical tips for optimization of ultrasound, CT, and MRI with MRCP in children; and image interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
(101 reference statements)
0
0
1
1
Order By: Relevance
“…CT scan on the other hand offers rapid imaging as well as providing detailed quality information with regard full extent of pancreatitis‐associated complications. CT scan is a first‐choice imaging study in children with certain US scanning limitation(s) – that is, air‐filled distended bowel loops or large body habitus 34–36 . In this study we however found no robust association(s) between the imaging findings in acute pancreatitis and mortality.…”
Section: Discussioncontrasting
confidence: 65%
“…CT scan on the other hand offers rapid imaging as well as providing detailed quality information with regard full extent of pancreatitis‐associated complications. CT scan is a first‐choice imaging study in children with certain US scanning limitation(s) – that is, air‐filled distended bowel loops or large body habitus 34–36 . In this study we however found no robust association(s) between the imaging findings in acute pancreatitis and mortality.…”
Section: Discussioncontrasting
confidence: 65%
“…Autores suscitan que las consecuencias de la lesión pancreática en personas con COVID-19 pueden verse agravadas debido a la inflamación sistémica y el síndrome de dificultad respiratoria aguda (SDRA), que ya son afectados por la infección directa de SARS-CoV-2 (4). La ecografía abdominal, la tomografía computarizada (TC), la resonancia magnética (RM), la colangiopancreatografía por resonancia magnética (MRCP) y la colangiopancreatografía endoscópica retrógrada (ERCP) son diversos métodos utilizados para el diagnóstico de la AP, los cuales son utilizados según las características de cada paciente y tienen cada uno sus ventajas y desventajas en términos de precisión diagnóstica, seguridad, invasividad y costo (5). En cuanto al manejo de esta patología, los principales tratamientos utilizados son la nutrición temprana y apropiada, el manejo del dolor con uso de estupefacientes como la morfina y la rehidratación intravenosa o fluidoterapia (6).…”
Section: Introductionunclassified